Efektivitas Penggunaan Media Pembelajaran Interaktif Berbasis Powtoon Terhadap Hasil Belajar Matematika Siswa Kelas IV SD - Awaluddin Muin; Firdaus Firdaus; Sitti Hajar (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
This research is a type of quantitative research with a pre-experimental research design. The purpose of this study was to determine students' mathematics learning outcomes and to determine whether or not there were significant differences before and after the use of powtoon-based learning media. The results showed that there were significant differences before and after learning using Powtoon-based learning media on the Mathematics learning outcomes of fourth grade students of SD Inpres 6/75 Bukaka, Bone Regency. So that Powtoon-based learning media is effective for improving mathematics learning outcomes for fourth grade students at SD Inpres 6/75 Bukaka Bone Regency.